PENGARUH KECEMASAN TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS DI WILAYAH PUSKESMAS BANYUANYAR SURAKARTA - Murdiningsih, Dyah Surti (JURNAL TALENTA PSIKOLOGI, 2013)
Health problems tend to increase, mental health is an issue that most real improvement. Some physical illnesses can cause anxiety in a person. A person with a chronic disease, prone to anxiety sufferers Diabetes is one of them. The purpose ofthis study is the effect ofanxiety on blood glucose levels in people with diabetes mellitus in Surakarta Banyuanyar Regional Health Center. Hypothesis There is apositive effect of anxiety on blood glucose levels in people with diabetes mellitus in the PHC Banyuanyar Surakarta. In this study sample was respondents with Diabetes Mellitus (DM) type 2 Surakarta region Banyuanyar Health Center. By sampling the total sampling with gauge Scale anxiety scaleand blood glucose levels of people with Diabetes Mellitus (DM) Type 2. Based on calculations using the computer program SPSS 15.0 for Windows obtained the value ofr count (0.754)> r table (0.339) or (p = 0.000 <0.05) so that Ha is accepted, it meansa significant difference between the levels of anxiety blood glucose in patients with diabetes mellitus in the Greater Surakarta Banyuanyar Health Center. Distribution results based on Blood Glucose Levels ofrespondents can be seen that the most dominant is the Blood Glucose Levels respondents in the category DM (â‰¥ 200) that is equalto 16 or 47.1%.